Manejo de espacio en dentición primaria y mixta - Hernández, Jesús Alberto; Gardeazabal, Luis Ernesto (Revista Estomatología, 1992)
The main purpose of the article was to examine the early loss of temporal teeth, as a loss factor causing the decreasement of dental arch's perimetre. At the same time to describe the equipment most commonly used for opening spaces because of the unique or multiple loss of temporal teeth.